EXOSC5 as a Novel Prognostic Marker Promotes Proliferation of Colorectal Cancer via Activating the ERK and AKT Pathways - Pan, Hongda; Pan, Jingxin; Song, Shibo; Ji, Lei; Lv, Hong; Yang, Zhangru (Frontiers in Oncology, 2019)
Background and Objective: Exosome component 5 (EXOSC5) is a novel cancer-related gene that is aberrantly expressed in various malignances. However, the molecular mechanism and biological role of EXOSC5 have not been explored in colorectal cancer (CRC). In this study, we investigated the functions and mechanisms by which EXOSC5 promotes the progression of CRC. Methods: EXOSC5 expressions in CRC cell lines and paired CRC and adjacent normal tissues were measured via quantitative real-time PCR (qRT-PCR), Western blot and immunohistochemistry (IHC). In vitro experiments including colony formation, Cell Counting Kit-8 (CCK-8), and flow cytometry and in vivo tumorigenesis assay were performed to explore the effects of EXOSC5 on growth of CRC. The impacts of EXOSC5 on ERK and Akt signaling pathways were measured by Western blot. Results: The mRNA and protein expression levels of EXOSC5 were up-regulated in CRC as compared to adjacent normal tissues. IHC analysis indicated that high EXOSC5 level was positively associated with poor prognosis. EXOSC5 overexpression facilitated the growth of CRC cells, while EXOSC5 knockdown led to decreased proliferation, G1/S phase transition arrest. The oncogenic functions of EXOSC5 were associated with activation of the ERK and Akt pathways in CRC. Conclusion: EXOSC5 is overexpressed in CRC and promotes CRC growth partly through activation of ERK and Akt signaling pathways. Accordingly, EXOSC5 may be a novel oncogene, and acts as a therapeutic target, or prognostic factor for CRC.